2022
DOI: 10.1177/08902070221076902
|View full text |Cite
|
Sign up to set email alerts
|

Openness to experience is stable following adversity: A case-control longitudinal investigation

Abstract: Although many people retrospectively report feeling more open-minded after experiencing highly stressful events, relevant longitudinal studies are scarce and have yielded contradictory findings. The present study used a 12-month longitudinal case-control design to test whether growth in openness (assessed every 4 months using multiple methods) occurs following major stressors, and whether changes relate to clinical symptoms of depression and/or posttraumatic stress. To do so, we compared participants (a) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 110 publications
1
5
0
Order By: Relevance
“…Our findings align with prior research that showed stability in a variety of outcomes following an event (Milojev et al, 2014;Chopik et al, 2021Chopik et al, , 2022Blackie and McLean, 2022;Fassbender et al, 2022;Forgeard et al, 2022;Jayawickreme et al, 2022;Reitz et al, 2022) and thus provide further evidence that stability in well-being is the more typical response to major life events (e.g., Infurna et al, 2022;Laceulle et al, 2022;Serrano et al, 2022). Furthermore, in line with growing longitudinal evidence, our results fail to detect evidence for possible post-traumatic growth following major life stressors, insofar as such growth might relate to a broad range of different aspects of well-being (Davis et al, 2021;Rakhshani and Furr, 2021;Dorfman et al, 2022;Infurna et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings align with prior research that showed stability in a variety of outcomes following an event (Milojev et al, 2014;Chopik et al, 2021Chopik et al, , 2022Blackie and McLean, 2022;Fassbender et al, 2022;Forgeard et al, 2022;Jayawickreme et al, 2022;Reitz et al, 2022) and thus provide further evidence that stability in well-being is the more typical response to major life events (e.g., Infurna et al, 2022;Laceulle et al, 2022;Serrano et al, 2022). Furthermore, in line with growing longitudinal evidence, our results fail to detect evidence for possible post-traumatic growth following major life stressors, insofar as such growth might relate to a broad range of different aspects of well-being (Davis et al, 2021;Rakhshani and Furr, 2021;Dorfman et al, 2022;Infurna et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…The importance of assessing longitudinal (positive) change following major life events is evident in studies that have tracked outcomes across time. Such studies show remarkable stability pre- and post-event across a range of outcomes, including empathy, life satisfaction, religiosity, and personality ( Milojev et al, 2014 ; Chopik et al, 2021 , 2022 ; Blackie and McLean, 2022 ; Dorfman et al, 2022 ; Fassbender et al, 2022 ; Forgeard et al, 2022 ; Jayawickreme et al, 2022 ; Reitz et al, 2022 ). Thus, stability or declines in functioning appear to be the more typical response to adversity, with growth or positive change being much less prevalent than suggested by prior cross-sectional research ( Frazier et al, 2009 ; Davis et al, 2021 ; Rakhshani and Furr, 2021 ; Gander and Wagner, 2022 ; Infurna et al, 2022 ; Laceulle et al, 2022 ; Serrano et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, the common theme across these papers is there was little longitudinal evidence for personality growth on average. Forgeard et al (2022) found that, on average across individuals, openness to experience remained stable over 12 months after recent and major life stressors when assessing multiple indicators for openness in a longitudinal case–control design, which compared individuals who had experienced a major stressor and (high or low) distress symptoms to control individuals with low distress and no major life stressor in the 2 years prior to the study. Blackie and McLean (2022) found little evidence to support average personality growth in the traits of empathy, humility, and compassion after individuals repeatedly narrated their interpersonal transgressions against their romantic partner over the course of 12 months.…”
Section: A Personality Science Approach To the Study Of Post-traumati...mentioning
confidence: 99%